Sustainable fashion transition towards net-zero future: A review of digital and material innovations, policies and regulatory framework - Benjamin Tawiah; Erin Cho; Emmanuel A. Ofori; Minyoung Suh; Bin Fei (Sustainable Futures)
The fashion industry has long been linked to complex social and environmental issues like labour exploitation, resource depletion, and carbon emissions. In alignment with the Sustainable Development Goals (SDGs) 8, 12, 13, and 15, various sustainable fashion initiatives have emerged to mitigate the industry's impact on the economy, society, and the environment. While there has been extensive research on sustainable fashion, there are limited studies that simultaneously investigate the geospatial collaborative networks alongside a comprehensive systematic review of the digital and material innovations, policies, and regulatory frameworks that facilitate the transition to a net-zero future. This integrative systematic review critically examines the advancements in sustainable fashion transition towards net-zero over the last two decades. It was found that recent efforts in digital, materials, and process innovations, along with the enforcement of existing policies and regulatory interventions are accelerating the transition towards net-zero for the achievement of the ''Fashion Pact 2050″. The findings suggest that collaboration and partnerships are essential for advancing sustainable fashion, as they enable fashion brands, NGOs, and governmental entities to unite their diverse expertise to drive innovation and share best practices. Such collective efforts enhance the impact of sustainability initiatives, fostering a more effective transition toward a net-zero future in the industry. This article further provides practical recommendations and implications for industry, academia, and governments for accelerating the transition to net-zero fashion; making it a useful material for researchers, fashion businesses, funding organizations, and policymakers.